Reduced antiviral gene expression and elevated CXCL8 expression in peripheral blood are associated with severe hypoxemia in RSV-infected children - Pita-Martínez, Carlos; Goez-Sanz, Carmen; Virseda-Berdices, Ana; Gonzalez-Praetorius, Alejandro; Mazario-Martín, Esther; Rodriguez-Mesa, María; Quero-Delgado, Marta; Matías, Vanesa; Martínez, Isidoro; Resino, Salvador (Frontiers in Immunology, 2024)
The pathology of respiratory syncytial virus (RSV) infection remains unclear. An unbalanced immune response to RSV infection can lead to immunopathology, causing airway damage and impaired exchange of oxygen and carbon dioxide between the air and the bloodstream. We aimed to evaluate the association of the expression of inflammatory and antiviral genes in peripheral blood with severe hypoxemia in children with RSV infection seen in the hospital emergency room. We conducted a cross-sectional study on 121 RSV-infected children seen in the hospital emergency rooms between 2015-2023. Total RNA was extracted from whole blood samples, and gene expression (IL-6, TNFα, CXCL8, ISG15, IFIT1, RIGI, IFNβ, CCL5, and CXCL10) was quantified using quantitative RT-PCR. The outcome variable was having severe hypoxemia (SpO2 ≤90%). The association analysis was performed using a volcano plot, adjusted logistic regression, and orthogonal partial least squares discriminant analysis (OPLS-DA). We found that 26 of 121 children had severe hypoxemia (SpO2 ≤90%). CXCL8 was overexpressed (fold changes (FC) >2; q-value <0.05), and ISG15, IFIT1, RIGI, IFNβ, CCL5, and CXCL10 were underexpressed (FC <-2; q-value <0.05) in children with severe hypoxemia. These associations were ratified using adjusted logistic regression. The OPLS-DA showed that the gene expressions of CXCL8, ISG15, IFIT1, RIGI, and CXCL10 had values of variable importance in projection (VIP) ≥1, being the most relevant features. In conclusion, an imbalance favoring inflammation over antiviral defense may contribute to the pathogenesis of severe hypoxemia in RSV-infected children. These findings provide valuable insights into the pathology of RSV infection.